The effect of the global financial crisis on the asymmetric relationship between exchange rate and stock prices. Issue 3 (28th March 2019) - Bhutto, Niaz A.; Chang, Bisharat H.
Abstract: This study replicates previous studies in the context of China by determining whether exchange rate changes have a symmetric or asymmetric effect on stock prices. Moreover, it extends previous studies by examining whether the relationship between the underlying variables changes as a result of the global financial crisis. For this purpose, we use both linear and nonlinear ARDL models during the full sample, pre‐crisis, and the post‐crisis periods. The findings of this study suggest that exchange rate asymmetrically affects the stock prices in the long run only when the whole sample period is selected, whereas it symmetrically affects both in the long run and in the short run during the pre‐crisis period and asymmetrically affects both in the long run and in the short run when the post‐crisis period is selected. These findings indicate that the financial crisis causes asymmetric relationship between exchange rate changes and stock prices and may, therefore, be taken into consideration while making investment or policy decisions.